2022
DOI: 10.1097/cce.0000000000000770
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Extracorporeal Membrane Oxygenation in COVID-19–Induced Acute Respiratory Distress Syndrome: An Inverse Probability Weighted Analysis

Abstract: IMPORTANCE:Although venovenous extracorporeal membrane oxygenation (VV ECMO) has been used in case of COVID-19 induced acute respiratory distress syndrome (ARDS), outcomes and criteria for its application should be evaluated. OBJECTIVES:To describe patient characteristics and outcomes in patients receiving VV ECMO due to COVID-19-induced ARDS and to assess the possible impact of COVID-19 on mortality. DESIGN, SETTING AND PARTICIPANTS:Multicenter retrospective study in 15 ICUs worldwide. All adult patients (> 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…In general, significant complications related to ECMO treatment are reported to be related to hemorrhage [12], just as in COVID-19 patients [13][14]. For intracerebral hemorrhage, many studies have reported incidence rates ranging from 2.3% to 17.4% [9,11,[15][16][17][18][19][20][21], with some reporting incidence rates as high as 41.7% [22]. In addition, ischemic stroke has been reported to have an incidence of 0.7 to 7 [9,11,[15][16][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, significant complications related to ECMO treatment are reported to be related to hemorrhage [12], just as in COVID-19 patients [13][14]. For intracerebral hemorrhage, many studies have reported incidence rates ranging from 2.3% to 17.4% [9,11,[15][16][17][18][19][20][21], with some reporting incidence rates as high as 41.7% [22]. In addition, ischemic stroke has been reported to have an incidence of 0.7 to 7 [9,11,[15][16][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…In the development of pneumothorax, previous studies reported the incidence rate was 11 and 12.6 [15,23], and the present results were similar to slightly lower rates. For pulmonary thromboembolism, various studies have reported incidence rates ranging from 1.6% to 19% [11,[15][16][17][18][23][24], with some reporting rates of over 60% [25][26]. In light of these circumstances, the incidence of pulmonary thromboembolism in Japan is confirmed to be relatively low.…”
Section: Discussionmentioning
confidence: 99%